Does the Political Context Shape How “Due Impartiality” is Interpreted? An Analysis of BBC Reporting of the 2019 UK and 2020 US Election Campaigns - Ceri Hughes (Journalism Studies, 2023)
Balance and impartiality are central principles in journalism, but this study argues their conceptual application in news reporting should be subject to more academic scrutiny. In the UK, the way “due impartiality” has been applied and regulated by broadcasters has raised concerns about promoting a ‘she-said-he-said’ style of reporting, which constructs balance but not scrutiny of competing claims. In this study, we analyse how the UK’s “due impartiality” was applied by journalists in different political contexts by assessing how the BBC dealt with competing party-political claims. We develop a nuanced quantitative analysis of BBC journalist interactions (N = 967) with claims made by the four main party leaders during the 2019 UK and 2020 US elections. Overall, we found BBC reporting robustly challenged claims by US politicians, whereas coverage of UK politicians often only conveyed claims and counterclaims with limited journalistic intervention, particularly on television news. We argue that impartiality should be viewed more as a fluid than fixed concept given that the context shapes how it is applied. As concerns about misinformation have grown over recent years, we conclude that more finely tuned studies are needed to understand how journalists apply concepts about balance and impartiality in political reporting.